Penerapan Terapi Gambar Terstruktur untuk Meningkatkan Atensi dan Regulasi Emosi pada Klien ODGJ di PSR-GPODGJ - Amirah Meta Wiyana; Sawi Sujarwo (Yayasan Kawanad, 2026)
Cognitive difficulties, including thought disorganization and problems with emotional regulation, may occur among people with mental disorders (PMD). This study aimed to evaluate the application of Structured Drawing Therapy in supporting sustained attention and emotional regulation among PMD clients at the Social Rehabilitation Center for Vagrants, Beggars, and People with Mental Disorders (PSR-GPODGJ) in South Sumatra Province, Palembang. The study employed a descriptive qualitative case study involving three clients, namely DR, DC, and Z, who showed attention difficulties, hallucinations, and emotional instability. The intervention was conducted in two main sessions. Session 1 focused on cognitive stimulation and reality orientation through thematic drawing activities, while Session 2 focused on fine motor control and frustration tolerance through line-drawing and shading activities involving geometric and floral patterns without the use of an eraser. The evaluation results indicated improvements in sustained attention, task independence, tolerance of mistakes, and behavioral control during the activities. For some clients, hallucinatory symptoms were not observed while the intervention activities were being conducted. The structured and repetitive drawing activities also provided clear task boundaries that helped the clients maintain attention and complete the activities. These findings suggest that Structured Drawing Therapy has potential as a supportive activity in psychosocial rehabilitation for PMD clients. However, further evaluation using systematic measures is needed to assess changes in attention and emotional regulation more accurately.